Observations of diffuse radio emission in the Abell 773 galaxy cluster - Sichone, Gift L (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
In this thesis, we present 18 and 21 cm observations of the A773 galaxy cluster observed with the Westerbork radio telescope. The final 18 and 21 cm images achieve a noise level of 0.018 mJy beam"¾ 1 and 0.025 mJy beam-1 respectively. After subtracting the compact sources, the low resolution images show evidence of a radio halo at 18 cm, whereas its presence is more uncertain in the low resolution 21 cm images due the presence of residual sidelobes from bright sources. In the joint analysis of both frequencies, the radio halo has a 5.37 arcmin2 area with a 6.76 mJy flux density. Further observations and analysis are, however, required to fully characterize its properties.
Keywords: Galaxies -- Clusters -- Observations; Radio astronomy -- Observations; Astrophysics -- South Africa; Westerbork Radio Telescope; A773 galaxy cluster; Astronomy -- Observations; Radio sources (Astronomy